(3GdEOGQI hGdJMdjd GdeGdj (B/s - (3GdYUGQ, QTGOs; (3GdCNQS, YGWa hBNQhfs ((3YeGf(B: s (3OGQ GdHQcI(B, s, 2001)
(3GdEOGQI GdeGdjI,GdJWhQ GdJGQjNj ddEOGQI,GdSjGSGJ GdeGdjI,eUGOQ GdJehjd,GdYhGed GdeMOOI dCfhGY GdJehjd,EOGQI QCS GdeGd GdYGed,EOGQI GdfbO GdLGgR,EOGQI GdeNRhf GdSdYj,EOGQI GdehLhOGJ GdKGHJI,eaghe GdJMdjd GdeGdj,GSJYeGdGJ GdJMdjd GdeGdj,COhGJ GdJMdjd GdeGdj,GdJMdjd GdebGQf ddbhGFe GdeGdjI,GdJMdjd GdebGQf HGdESJfGO Edi Qbe bjGSj,JMdjd bGFeI eUGOQ GdCehGd hGSJNOGeGJgG,GdfSH GdeGdjI,JMdjd GdJYGOd,JMdjd GdQaY,GdQaY GdJTZjdj, GdQaY GdeGdj, GdQaY GdeTJQc,eaghe GdJNWjW GdeGdj,GdaGFOI GdHSjWI hJWHjbGJgGs
(3HHdjhZQGajG U(B.375 (3GdedGMb U(B.357s
Keywords: (3GdEOGQI GdeGdjIs